2013
DOI: 10.1159/000350544
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Intravitreal Dexamethasone Implant for Retinitis Pigmentosa-Related Macular Edema

Abstract: Purpose: To report the efficacy of intravitreal dexamethasone implant in a patient with retinitis pigmentosa and bilateral cystoid macular edema unresponsive to topical carbonic anhydrase inhibitors. Case Report: A 36-year-old man with bilateral cystoid macular edema associated with retinitis pigmentosa that was unresponsive to topical carbonic anhydrase inhibitors underwent bilateral 0.7-mg intravitreal dexamethasone implants two weeks apart. Spectral domain optical coherence tomography revealed resolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
(17 reference statements)
0
17
0
2
Order By: Relevance
“…10,11,12,13 Srour et al 10 administered intravitreal dexamethasone implant in 3 patients with mean central macular thickness (CMT) of 443±185 µm (range 213-619 µm) and mean visual acuity of 20/160 (20/50-20/200) at baseline. One month after dexamethasone implantation, mean CMT improved to 234±68 µm and mean BCVA improved to 20/100.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11,12,13 Srour et al 10 administered intravitreal dexamethasone implant in 3 patients with mean central macular thickness (CMT) of 443±185 µm (range 213-619 µm) and mean visual acuity of 20/160 (20/50-20/200) at baseline. One month after dexamethasone implantation, mean CMT improved to 234±68 µm and mean BCVA improved to 20/100.…”
Section: Discussionmentioning
confidence: 99%
“…One month after dexamethasone implantation, mean CMT improved to 234±68 µm and mean BCVA improved to 20/100. Saatci et al 11 reported a case with bilateral ME secondary to RP. Visual acuity of the patient was 2/10 in both eyes and he had been under topical dorzolamide treatment 3 times a day for nearly a year without any change in VA. One week after the injection his visual acuity improved to 4/10 and ME resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Il existe 3 cas rapportés dans la littérature d'OM compliquant des rétinopathies pigmentaires traités par injection d'implant de dexaméthasone [35][36][37], et une petite série rétrospective de 4 yeux [38]. Tous décrivent une efficacité sur la réduction d'épaisseur maculaire, mais parfois sans succès fonctionnel, et avec une tendance à la récidive dès 2 à 3 mois après l'injection [35,38].…”
Section: Discussionunclassified
“…Tous décrivent une efficacité sur la réduction d'épaisseur maculaire, mais parfois sans succès fonctionnel, et avec une tendance à la récidive dès 2 à 3 mois après l'injection [35,38].…”
Section: Discussionunclassified
“…The previous reports on intravitreal steroid administration in eyes with RP-related CME [30][31][32][33][34][35][36][37][38][39] are summarised in Table 1. The treatment effect of dexamethasone implant can be seen in a case with bilateral RP-related CME (Figures 1 and 2).…”
Section: -30mentioning
confidence: 99%